2022
DOI: 10.1016/j.bcp.2021.114618
|View full text |Cite
|
Sign up to set email alerts
|

Role of 27-hydroxycholesterol and its metabolism in cancer progression: Human studies

Abstract: Direct translation of findings achieved in experimental cell or animal models to humans is quite a difficult task. We focused here only on the epidemiological and ex vivo human studies so far available about the role of 27hydroxycholesterol (27OHC) and related metabolism in cancer development. Some studies point to an adverse effect of 27OHC in breast cancer, based on the oxysterol's recognized ability to bind to and modulate estrogen receptors. The detrimental role of this side chain oxysterol would be eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The expressions of key enzymes involved in 27‐HC metabolism, namely, CYP27A1 and CYP7B1, 9 in breast tissues and their correlation with G9a were assessed in both premenopausal and postmenopausal women with breast cancer of tumour grade 2 and grade 3. CYP27A1 synthesizes 27‐HC, whereas CYP7B1 catabolizes 27‐HC, 9 thus reducing its levels. Of the 87 samples from patients with breast cancer, 68 were ER‐positive and 19 were ER‐negative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expressions of key enzymes involved in 27‐HC metabolism, namely, CYP27A1 and CYP7B1, 9 in breast tissues and their correlation with G9a were assessed in both premenopausal and postmenopausal women with breast cancer of tumour grade 2 and grade 3. CYP27A1 synthesizes 27‐HC, whereas CYP7B1 catabolizes 27‐HC, 9 thus reducing its levels. Of the 87 samples from patients with breast cancer, 68 were ER‐positive and 19 were ER‐negative.…”
Section: Resultsmentioning
confidence: 99%
“…At the clinical level, the role of 27‐HC is yet to be elucidated. CYP7B1, the key enzyme responsible for the catabolism of 27‐HC, is associated with increased recurrence‐free survival, 8 whereas the expression of the 27‐HC synthesising enzyme CYP27A1 is linked to unfavourable tumour characteristics 9‐12 . A study has demonstrated that the serum 27‐HC level does not correlate with its levels in breast tumours, unlike in normal breast tissue, suggesting a possible association of dysregulation of 27‐HC metabolism in breast cancer cells 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it needs to be noted that 27-HC plays a role in a number of other mechanisms including: reduction of P53 transcriptional activity [ 37 ], production of reactive oxygen species (ROS) leading to STAT3 activation, and VEGF signaling resulting in induced angiogenesis [ 38 , 39 ], induction of epithelial-mesenchymal transition (EMT) [ 39 , 40 ], and secretion of chemokines enhancing the production of macrophages which in turn further produce 27-HC [ 39 ]. 27-HC is also a ligand to several other receptors including sterol regulatory element binding protein (SREBP), peroxisome proliferator-activated receptors (PPARs), retinoic acid receptor related orphan receptor (ROR), toll like receptors (TLRs), and insulin-induced gene 1 protein (INSIG) [ 41 , 42 ], leaving the possibility that other -previously undetected- mechanisms may have an impact on the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of 27-OH-Chol in ER-positive breast cancer was up to six-fold higher than the adjacent normal tissue. Such an increased concentration was negatively associated with disease-free survival, mainly in post-menopausal women, probably because of its agonistic action [40,41]. Furthermore, 27-OH-Chol may indirectly promote tumor growth and metastasis spread by decreasing immune surveillance [42].…”
Section: Cholesterol Derivativesmentioning
confidence: 99%